Aerosols optical thickness estimation from MODIS sensor images over Perú (2004-2005) - Cholan, E. (2017)
In the present work we estimate the aerosols optical thickness (AOT) in the wavelength of 0.55µm using the mod021km - level 1B Calibrated Radiances - 1km images as input of the SBDART radiative transfer model [1]. The study area is Peru in the geographic latitudes 0 to 20°S and the geographic longitudes of 82 to 68°O. The SBDART model simulates the radiative transfer in the atmosphere (scattering, absorption, emission, etc.), estimating the irradiance in the top of the atmosphere and on the Earth surface. The two-stream and Eddington approximations are used to solve the radiative transfer equation, considering a parallel plane atmosphere. This model generate equations deﬁning the AOT of 0.55µm as a function of the reﬂectance at the top of the atmosphere (TOA) for the band 1 at 0.66µm of the MODIS sensor.The 0.55 µm AOT estimated by the SBDART model was verify with the 0.55µm AOT data measured in-situ from an AERONET network station located in Rio Branco, Brazil, for the both year 2004 and 2005.The station is located at latitude 9.954°S and longitude 67.869°O. The dispersion dataplot of the time series of both AOT showed a (not) signiﬁcant correlation of 0.99 (0.06) for the year 2004 and 2005.Also, was verify the AOT obtained from the MODIS images (MOD04_L2) with the AOT estimated by the SBDART model, the scatter plot of the time series of both AOT showed a signiﬁcant correlation of 0.99 for both year 2004 and 2005, while the veriﬁcation of the AOT from the MODIS images (MOD04_L2) with the 0.55µm AOT data in-situ from Rio Branco, show in the dispersion dataplot of the time series an (not) signiﬁcant correlation of 0.98 (0.02) for the year 2004 and 2005. The SBDART model used for estimating the AOT is limited to the Central and Southern part of Peru, due to its geographic location, meteorological conditions, atmospheric circulation and optical properties of aerosols. Keywords: SBDART, MODIS, aerosols, optical thickness, AERONET.